'The sounds turn somersaults and the harmonica is mourning…': The healing effects of music making. (1st December 2022) - Hochreutener, Sandra Lutz
Children love making music – or, as we say in music therapy, they love playing with music. At the same time both joyful and sincere, they explore the sounds of the instruments and try out different tunes and rhythms as a way of expressing their feelings and interacting with others. Through play, they create inexhaustible, inventive musical scenarios which in turn enable them to develop a better understanding of their own personal circumstances and thereby to grow and set themselves free. This keynote will provide insights into the ways in which music therapy can assist personal growth by tapping into the child's ability to engage with music in a spontaneous and playful way.